STUDENTS' ABILITY TO WORK ON MULTIPLE CHOICE SCIENCE QUESTIONS IN CLASS VII USING THE RASCH MODEL - Ganesha, Anenda Bagus Satrya; Dahlan, Tina Hayati; Hidayati, Salila Prasidya (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2024)
This study aim to assess the ability of seventh-grade student to solve multiple choice science questions using the Rasch Model. A descriptive quantitative approach was employed, utilizing an instrument to consisting of 30 science questions aligned with the Kurikulum Merdeka. The sample comprised 75 junior high school students in Bandung City, selected through non probability sampling. The results indicated that participant 49 demonstrated the highest ability, whereas participants 15 and 22 as the lowest abilities. Question number 21 was identified as the most difficult, while question number 5 was the easiest. The Rasch Model revealed a high reliability of the questions, with a coefficient of 0.91. furthermore, the analysis indicated that question number 4,11,12,13,14,15, and 18 had low validity and should be discarded. Additionally, the Rasch Model was able to identify students who were potentially cheating during the test. These findings confirm that the Rasch Model is viable tool for evaluating the quality of test questions before they are administrated to students.